The auger snails (Gastropoda, Conoidea, Terebridae) of the Miocene Paratethys Sea - Harzhauser, Mathias; Landau, Bernard M. (Zootaxa, 2023)
We present a critical review of the Miocene Terebridae of the European Central Paratethys Sea. In total, we document 23 species placed in 7 genera. We designate lectotypes for Terebra bigranulata Hoernes & Auinger, 1880 [= Fusoterebra terebrina (Bellardi & Michelotti, 1840)], Terebra (Hastula) cinereides Hoernes & Auinger, 1880 [= Hastula duboisiana (d’Orbigny, 1852)], Terebra (Myurella) lapugyensis Hoernes & Auinger 1880 [= Hastula lapugyensis (Hoernes & Auinger, 1880)] and Terebra transylvanica Hoernes & Auinger, 1880. Based on conchological similarities we assume that the extant terebrine Punctoterebra Bartsch, 1923 might be a subjective junior synonym of Strioterebrum Sacco, 1890. In this case, molecular data could resolve this question, as Strioterebrum is still represented today by Strioterebrum reticulare (Sacco, 1891). Hastulopsis Oyama, 1961 and Maculauger Fedosov, Malcolm, Terryn, Gorson, Modica, Holford & Puillandre, 2020 are recorded for the first time from the European Neogene. Terebra golebiowskii nov. sp. and Oxymeris transleithana nov. sp. are introduced as new species.